Characterizing antimicrobial resistance and plasmidome diversity in Escherichia coli from imported frozen broiler chicken in the United Arab Emirates - Habib, Ihab; Mohamed, Mohamed-Yousif Ibrahim; Lakshmi, Glindya Bhagya; Ghazawi, Akela; Khan, Mushtaq; Khalifa, Hazim O. (Frontiers in Microbiology, 2025)
IntroductionThe global increase in antimicrobial-resistant (AMR) Escherichia coli in the poultry supply chain poses significant food safety and public health risks. This study aims to assess the AMR profiles and plasmid content of E. coli isolated from imported frozen broiler carcasses available in the United Arab Emirates (UAE) market.MethodsA total of 253 frozen whole broiler carcasses imported from Brazil, France, Oman, and Ukraine were screened for the presence of E. coli. Antimicrobial susceptibility testing was conducted on 90 isolates. Whole-genome sequencing (WGS) was performed on 33 representative isolates to analyze sequence types (STs), resistance genes, and plasmid content using the MOB-suite pipeline.ResultsE. coli was detected in 248 out of 253 samples. Resistance to ampicillin (52.2%) and tetracycline (35.6%) was most common, with 68.9% of isolates exhibiting multidrug resistance (MDR). WGS revealed 22 STs, with ST1564 being the most prevalent (12.1%). Clinically relevant ST10 and ST58 were also identified. Extended-spectrum β-lactamase (ESBL) genes blaCTX–M–55 and blaCTX–M–8 predominated, often co-occurring with fluoroquinolone resistance genes qnrS1 and qnrB19. A total of 197 plasmids were identified; 63.6% were classified as conjugative. The most frequent relaxase types were MOBP (37 plasmids) and MOBF (24 plasmids), with IncI-gamma/K1 and IncF plasmids commonly linked to ESBL genes.DiscussionThis study provides one of the first genomic characterizations of plasmid-mediated AMR in poultry-associated E. coli in the Middle East. The high prevalence of MDR and mobile resistance elements underscores the role of international poultry trade in AMR dissemination. These findings highlight the need for strengthened AMR surveillance and improved regulatory control over antibiotic use in poultry production to mitigate public health risks.